Organic food processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Convenience and fast-foods occupy a growing share of many people s diets. To help producers of organic food to adjust to this trend, IFOAM, the International Federation of Organic Agriculture Movements will organise its first international seminar...